2017
DOI: 10.3928/01477447-20161013-04
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Rotator Cuff Tears: Ultrasound Versus Magnetic Resonance Imaging

Abstract: Ultrasound and magnetic resonance imaging (MRI) are both capable of diagnosing full-thickness rotator cuff tears. However, it is unknown which imaging modality is more accurate and precise in evaluating the characteristics of full-thickness rotator cuff tears in a surgical population. This study reviewed 114 patients who underwent arthroscopic repair of a full-thickness rotator cuff tear over a 1-year period. Of these patients, 61 had both preoperative MRI and ultrasound for review. Three musculoskeletal radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 52 publications
1
33
0
3
Order By: Relevance
“…Posterosuperior rotator cuff tears were diagnosed using MRI findings. In the previous general-population studies 2 , 27 , the existence of a rotator cuff tear was determined by ultrasound instead of MRI, which has higher interobserver reliability 57 . In addition, MRI findings are also more useful for diagnosing subscapularis tendon tears, so in the current study, we were able to exclude subscapularis tendon tears 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Posterosuperior rotator cuff tears were diagnosed using MRI findings. In the previous general-population studies 2 , 27 , the existence of a rotator cuff tear was determined by ultrasound instead of MRI, which has higher interobserver reliability 57 . In addition, MRI findings are also more useful for diagnosing subscapularis tendon tears, so in the current study, we were able to exclude subscapularis tendon tears 58 .…”
Section: Discussionmentioning
confidence: 99%
“…However, if the ultrasound is negative and there is ongoing clinical concern, MRI should be considered which is keeping in line with current algorithms used for rotator cuff imaging [8]. Although ultrasound has similar sensitivity and specificity compared to MRI when diagnosing some types of supraspinatus tendinopathy, MRI is shown to be better at accurately depicting the lesion size, medial retraction and degree of muscle fatty infiltration [16]. Partial thickness tears were where most of the discrepancy between ultrasound and MRI findings were in our study.…”
Section: Discussionmentioning
confidence: 88%
“…In fact, although MSUS provided high accuracy in the detection of rotator injuries compared to MRI; many clinicians prefer MRI as preoperative imaging than ultrasound because ultrasound provides less information regarding the morphology of torn ends of cuff muscles and the exact size and extent of tear [9]. Okoroha et al [10], retrospectively studied ultrasound and MRI of 144 patients who underwent arthroscopic repair of rotator cuff and showed that there is a greater difference between the two modalities in the measurement of tear size and retraction status and concluded that ultrasound is the imaging modality for detection of rotator cuff tear and MRI should be done for surgical planning of large tears. Also, Sipola et al…”
Section: Discussionmentioning
confidence: 99%